35.4k views
4 votes
F(x) = -x^2 - 10x - 13, find f(-2)

User Hele
by
4.5k points

1 Answer

3 votes

Answer: f(-2) = 11

Concept:

Here, we need to understand the idea of evaluation.

When encountering questions that gave you an expression with variables, then stated: "If x = a, y = b, z = c" (a, b, c are all constants), this means you should substitute the value given for each variable back to the expression.

Solve:

Given information

f (-2) or x = -2

Given function

f(x) = -x² - 10x - 13

Substitute values into the function

f(-2) = -(-2)² - 10 (-2) - 13

Simplify exponents

f(-2) = -(4) - 10 (-2) - 13

Simplify by multiplication

f(-2) = 4 + 20 - 13

Simplify by addition/subtraction

f(-2) = 24 - 13

f(-2) =
\boxed{11}

Hope this helps!! :)

Please let me know if you have any questions

User Sean Barbeau
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.